2021
DOI: 10.18857/jkpt.2021.33.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kinesio Taping on Balance and Gait in Patients with Stroke: A Systematic Review and Meta-Analysis of Studies in Korea

Abstract: The objective of this study was to investigate the effects of Kinesio taping (KT) for balance and gait in patients with stroke through meta-analysis of studies conducted in Korea. Methods: RISS, Science on, and DBPia were the three databases used to collect articles on KT. Keywords such as "Stroke," "Kinesio taping," "Elasticity taping," and "Taping" were used to search for published articles. We systematically searched from the inception of each database to November 2020. Interventions and comparisons were KT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
3
1
Order By: Relevance
“…The results of separate meta-analyses on each outcome revealed that effect size had the greatest effect on gait speed, followed by TUG and BBS. This finding is not consistent with the results of a previous meta-analysis to identify the effect of ankle Kinesio taping on balance and gait-related outcomes for stroke [18]. They reported a greater effect on balance than gait in the study, and this inconsistency between the previous and present studies is mainly thought to be because our analysis included studies that applied taping to body parts other than the ankle, as well as those that applied non-elastic taping.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of separate meta-analyses on each outcome revealed that effect size had the greatest effect on gait speed, followed by TUG and BBS. This finding is not consistent with the results of a previous meta-analysis to identify the effect of ankle Kinesio taping on balance and gait-related outcomes for stroke [18]. They reported a greater effect on balance than gait in the study, and this inconsistency between the previous and present studies is mainly thought to be because our analysis included studies that applied taping to body parts other than the ankle, as well as those that applied non-elastic taping.…”
Section: Discussioncontrasting
confidence: 99%
“…The taping method attached to the ankle and knee alone showed a medium effect size, whereas the taping method attached to the hip and trunk showed a small effect size on balance and gait. These results are consistent with the findings of previous studies that applying Kinesio taping only to the ankles of patients with stroke is relatively ineffective [18]. Gait impairment in patients with stroke is related to stiffness and weakness of the ankle and knee [52][53][54].…”
Section: Discussionsupporting
confidence: 92%
“…Such balance is an important ability in daily life and sports scenes. 3 Balance refers to the ability to maintain the center of gravity on the basal plane and maintain equilibrium when moving the body and occupies an important part in maintaining posture and performing motor skills. 4 There are many types of stretching, but static stretching is the most common stretching technique that can be easily done at home, while ballistic stretching is a risk of tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…Such taping therapy helps physical activity by relieving pain and balancing the body. [3][4][5] Kinesio taping is effective in suppressing or promoting muscle tension by attaching it to the skin of the relevant muscle to normalize the action of the main muscle that moves the joint. [5][6][7] Also, Kinesio taping is known as a safe treatment method due to its continuing effect and simple usage.…”
Section: Introductionmentioning
confidence: 99%